PENGARUH GAYA KEPEMIMPINAN DELEGATIF, PELATIHAN DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA KARYAWAN PADA PT. BUMEN REDJA ABADI CABANG DENPASAR TIMUR - Widari, I Gusti Ayu; Imbayani, I Gusti Ayu (Ekonis: Jurnal Ekonomi dan Bisnis, 2025)
Abstract: Human resources are one of the factors that are directly involved in running company activities and play an important role in improving employee performance in achieving predetermined goals. Human resources are required to be able to overcome all challenges and are expected to be able to take advantage of opportunities and be able to meet the demands of needs, especially those that exist or come from their work environment. This research was conducted at PT. Bumen Redja Abadi, East Denpasar Branch with the research objects being delegative leadership style, job training, non-physical work environment and employee performance. This study aims to determine and analyze the effect of delegative leadership style, training and non-physical work environment on employee performance at PT. PT. Bumen Redja Abadi, East Denpasar Branch. The population in this study were all employees of PT. Bumen Redja Abadi, East Denpasar Branch, totaling 35 people. The sampling technique used the census sampling technique, so the number of samples used was 35 people. Data collection techniques used observation, interviews, documentation, and questionnaires. The data analysis technique used to answer the hypothesis was multiple linear regression analysis. The results of this study indicate that delegative leadership style has a positive and significant effect on employee performance, training has a positive and significant effect on employee performance, non-physical work environment has a positive and significant effect on employee performance. The results of the determination coefficient analysis obtained were 0.735, which means that the variables of delegative leadership style, training and non-physical work environment provide information of 73.5% on employee performance, while the remaining 26.5% is explained by other variables not examined in this study. Keywords: Delegative Leadership Style, Training, Non-Physical Work Environment and Employee Performance